The Carpatho-Rusyn Movement in the 21st century in North America = Ruch karpatorusiński w XXI wieku w Ameryce Północnej - Best, Paul J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To be precise this essay deals, in the main, with the English speaking parts of North America - there is no known Carpatho-Rusyn activity in either the French or the Spanish areas. We discuss here the Carpatho-Rusyn orientation which sees the East Slavs of the Carpathian Mountains of Central Europe, and their descendants wherever found, as a unique population/ethnic group/nation not dependent on some other entity for its existence.
Keywords: Lemko; Carpatho-Rusin; North America; Łemkowie; Karpatorusini; Ameryka Północna